(untitled) (Iranian Journal of Kidney Diseases, 2009)
Introduction. This study was conducted to compare marital adjustment between patients on long-term hemodialysis and healthy controls and to determine whether the psychological symptoms correlate with marital adjustment in these patients. Materials and Methods. In a case-control study, 40 patients on long-term hemodialysis and 40 healthy participants were compared for the quality of marital relationship. The Revised Dyadic Adjustment Scale was used for interviews of marital relationship, which includes total marital adjustment and its subscales of marital consensus, affection expression, marital satisfaction, and marital cohesion. Symptoms of anxiety and depression and the Ifudu comorbidity scale were also assessed in the patients group. Results. Marital consensus, affection expression, marital satisfaction, marital cohesion, and the overall marital relationship were significantly poorer in the patients on hemodialysis than in the controls. Also, symptoms of anxiety were more severe among the patients on hemodialysis in comparison with that in the controls. However, this was not the case for symptoms of depression. In the patients on hemodialysis, the severity of anxiety slightly correlated reversely with the total marital relationship score and marital satisfaction subscale. Depression correlated reversely with total marital adjustment, affection expression, marital satisfaction, and marital cohesion. Finally, some marital relationship subscales showed poorer results in men on dialysis, younger patients, and those with higher educational levels. Conclusions. Marital adjustment in patients on hemodialysis, which is linked with depressive symptoms and anxiety, is poorer compared to the healthy controls. This finding shows the necessity of an appropriate family approach for patients on long-term dialysis.